GO-JEK: REGULATORY RESTRICTIONS AND LOCAL WISDOM’S CHALLENGERS FACED BY THE UNICORN - Hilman Lutfi (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
The digital revolution cannot be resisted or even avoided. Indonesia and its 263 million population (The World Bank Group, 2018)are now transitioning into the digital transformation era. Many sectors have been transformed, one of it is transportation industries. Go-Jek is one of Indonesia original startup that offers ride-hailing online transportation services. Its competitor, Grab, Singapore-based ride hailing online transportation services,is competing the same market in Indonesia. Moreover, they already penetrated through the Southeast Asia market. Today, Go-Jek is already dominating the Indonesiaride-hailing transportation with its 79.20% market share, compared to 21.80% owns by Grab. Leading the market is not the real definition of satisfaction, instead, they should maintain their current users while maximize their businesses to unlock the overall Indonesia potential, moreover, the Southeast Asia.The existence of Go-Jek on its origin country is not without challenges, there are so many pros and contras on each stratum.The conventional transportation organization drivers are seeing Go-Jek as their biggest threads to earn their living, while government is seeing Go-Jek from both advantages and disadvantages sides. Go-Jek could decrease the number of Indonesia unemployment, contributes to taxes, and positioned Indonesia as a competitive country that could competes globally in terms of digital economics. But on the other hand, the uncontrolled expansion of Go-Jek across Indonesia could leads to social conflict, both verbal and physical, which is must be avoided and prevented.In conclusion, there are several challenges that Go-Jek should face to guard and expand their businesses.